2021
DOI: 10.1016/j.vaccine.2021.08.083
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine uptake among healthcare workers in the fourth country to authorize BNT162b2 during the first month of rollout

Abstract: Background The Kingdom of Saudi Arabia (KSA) was the fourth country in the world to authorize the BNT162b2 coronavirus disease 2019 (COVID-19) vaccine, which it rolled out on December 17, 2020 and first targeted at healthcare workers (HCWs). This study assesses vaccine uptake among this group during the first month of its availability. Methods A national cross-sectional, pilot-validated, self-administered survey was conducted among HCWs in the KSA between December 27, 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 46 publications
9
41
4
Order By: Relevance
“…Most HCWs had had previous contact with COVID-19 patients, and 23.2% had been previously diagnosed with laboratory-confirmed COVID-19 themselves. This is a significant rise from previously published data in KSA of self-reporting the diagnosis of COVID-19 among HCWs, which was 10% overall [18]. In our study, 7.1% reported traveling internationally to countries with caseloads of the Delta variant, and international travel has been described as a risk factor for acquiring the Delta variant early in its emergence.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Most HCWs had had previous contact with COVID-19 patients, and 23.2% had been previously diagnosed with laboratory-confirmed COVID-19 themselves. This is a significant rise from previously published data in KSA of self-reporting the diagnosis of COVID-19 among HCWs, which was 10% overall [18]. In our study, 7.1% reported traveling internationally to countries with caseloads of the Delta variant, and international travel has been described as a risk factor for acquiring the Delta variant early in its emergence.…”
Section: Discussioncontrasting
confidence: 46%
“…The survey was a pilot-validated questionnaire sent through SurveyMonkey©, a platform that allows researchers to carry out surveys via the web. The survey was adapted from the one used in our previously published research, with modifications and additions related to the new Delta SARS-CoV-2 variant [15][16][17][18][19].…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, the acceptance rate among HCWs was 52.52% in Saudi Arabia, SA (December 2020) [ 9 ], and 48.6% in France and French speaking Belgium and Quebec (October–November 2020) [ 2 ]. These acceptance rates are higher than the 33.2% from SA (December–January 2020) [ 15 ], 24.5 to 36% from USA (September–October 2020) [ 16 ] and 27.7% from the Democratic Republic of Congo (March–April 2020) [ 14 ] but lower than the 64.9% reported acceptance rate from SA (October–November 2020) [ 17 ], 60–90% among physicians in Greece (February 2020) and 60% from the nurses in Hong Kong, China (February–March 2020) [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
“…COVID-19 vaccines were rolled out in the KSA on December 17, 2020, with mass campaigns in place and top country leaders posing as vaccine champions to boost the public’s trust in the vaccinations [ 43 ]. In recently published studies from Saudi Arabia, 66.7% of HCWs did not sign up to obtain the COVID-19 vaccine, and another study showed that only 24.4% and 20.9% were willing to receive the ChAdOx1 nCoV-19 and BNT162b2 vaccines, respectively [ 44 , 45 ]. Developing vaccine confidence among HCWs is a major step in stopping the pandemic amid all the misinformation that is available on different media platforms.…”
Section: Discussionmentioning
confidence: 99%